Граничное поведение кольцевых Q-гомеоморфизмов в метрических пространствах - Смоловая, Е.С. (Доповіді НАН України, 2010)
Дослiджується проблема продовження на межу так званих кiльцевих Q-гомеоморфiзмiв мiж областями в метричних просторах iз мiрами. Формулюються умови на функцiю Q(x) та межi областей, при яких усякий кiльцевий Q-гомеоморфiзм допускає неперервне або гомеоморфне продовження на межу. Результати застосованi, зокрема, до рiманових многовидiв, просторiв Левнера, груп Карно та Гейзенберга. The problem of extension to the boundary of the so-called ring Q-homeomorphisms between domains in metric spaces with measures is investigated. Conditions on functions Q(x) and boundaries of domains, under which every ring Q-homeomorphism admits a continuous or homeomorphic extension to the boundary, are formulated. These results are applicable, in particular, to Riemannian manifolds, the Loeuner spaces, the Carnot and Heisenberg groups.